First description of a D‐CE‐D hybrid gene on a weak D Type 2 molecular background. Issue 5 (5th February 2017) - Granier, Thomas; Chiaroni, Jacques; Bailly, Pascal; Silvy, Monique
Abstract : BACKGROUND: RhD phenotypes that express a significantly reduced amount of RhD antigen per red blood cell may be mistyped as RhD‐negative by standard serologic methods. The molecular identification of weak D Type 1, 2, or 3 carriers allows managing them as RhD‐positive and, thus, rationalizes the use of RhD‐negative stock units and the administration of Rh‐immunoglobulin prophylaxis, avoiding unnecessary costs and possible side effects. STUDY DESIGN AND METHODS: One sample was investigated for confirming a D−C−E+c+e− phenotype. Rh phenotyping was performed with the microplate direct hemagglutination test. DNA array analysis was performed using the BeadChip wRhD kit, and the RHD gene was explored by sequencing to determine the molecular background associated with RhD‐negative phenotype. RESULTS: Molecular investigations showed a lack of amplification of Exons 3 through 7 and c.1154G>T transversion in Exon 9, suggesting an RHD‐CE‐D composite on a weak D Type 2 background. We attempted to precisely identify the two recombination sites generating this hybrid allele. The 5′ and 3′ breakpoints were located in Introns 2 and 7, which showed concentration of mobile Alu sequences most likely involved in the RHD‐cE(3‐7)‐weak D Type 2 allele. CONCLUSION: Altogether, we identified the first example of an RHD‐CE‐D large hybrid allele on a weak D Type 2 background associated with an RhD‐negative phenotype. By investigating the RHCE‐D breakpoint zones, we suggest a mobile element‐mediated recombination.